A Bibliometric Analysis and Visualisation of Research Trends in Allergy of hip-implants - Kumar , Raman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A diversified set of metals are used for hip-implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Allergy of hip-implants”. All published articles related to “Allergy of hip-implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “Allergy of hip-implants” and also to find out the trends related to the same. The most active journals in this research domain were the Acta Orthopaedica and Journal of Orthopaedic Surgery and Research. The most active countries were the United States of America and the United Kingdom. The leading organization engaged in the research regarding allergy of hip-implants was the Hospital of Special Surgery, United States of America. The most active author who had made valuable contributions related to the allergy of hip implants was Thomas P.